Pelestarian dan Pengembangan Kampung Nikmat Cigugurgirang Sebagai Destinasi Wisata Warisan Budaya Gastronomi Sunda - Caria Ningsih; Dewi Turgarini (STIEPAR YAPARI Bandung, 2020)
Kampung Nikmat, located in Cigugurgirang Village, Bandung Regency, has people assets with special skills in culinary field (gastronomy). Especially the old ladiwes have abilities to make various Sundanese Foods. But there is no any effort to identify the food and preserve the culinary items in this area. The objective of this study is to identify and preserve the traditional Sundaneses food, then analyse its potential to become a Sundanese gastronomy tourism destination. The method of this research is qualitative method, through observation, depth interviews, documentation and Focus Group Discussion (FGD) with selected residents of Kampung Nikmat and gastronomy experts. The result of the study is an inventory of Sundanese gastronomy product in Kampung Nikmat, which is consist of 294 foods, 15 beverages and 15 various of sambal (chili souses). All of the items of the gastronomy products are able to be made by the old ladies of this village. The other result of this research is a design program of gastronomy tourism, that is involved a variety stakeholder, such as some residents, government, scholars, local dan foreign tourist. The design of the program is consisted of cooking class, sharing knowledge of the traditional Sundanese gastronomy products, then marketing days of the products as a series of Gastronomy Tourism.